Home is where the heart is: factors Determining family demand and its Implications for HRM practices - Kengatharan, N. (My University, 2020)
A plethora of studies on family demands that have been investigated in the Western countries are reflective of such cultural contexts limiting its applicability to another cultural context. The factors determining family demand where conflict originates are country-culture specific and consequently, anchored in the conservation of resource theory, the present study aims to discover the factors making a significant variance in family demand. Strongly based on the ontological and epistemological assumptions, the study adopted a survey strategy with a deductive approach in a cross-sectional time horizon. Data were garnered from 487 banking employees with a self–reported questionnaire. The present study reveals that hours spent on household chores, hours spent on childcare, hours spent on dependents, and gender have significantly impacted family demand, nonetheless, formal and informal organisational supports have alleviated the level of family demand. Remarkably, the study affirms the prevalence dogma of traditional gender role ideology and women’s position in a collectivist cultural context. Surprisingly, the number of children, number of dependents, marital status and age were not found as predictors of family demand. The findings of the study have proffered many useful practical implications for HRM practices.
Keywords: Conservation of resource theory; Family demand; Formal organisational support; Informal organisational support